Flow-cytometric cell sorting coupled with UV mutagenesis for improving pectin lyase expression - Fang, Ke; Ma, Jun; Wang, Xinyu; Xu, Ziting; Zhang, Ziyang; Li, Piwu; Wang, Ruiming; Wang, Junqing; Sun, Chuying; Dong, Ziyang (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Alkaline pectin lyase is an important enzyme with a wide range of applications in industrial production, It has been widely used in many important fields such as fruit juice processing and extraction, the dyeing and processing of cotton and linen textiles, degumming plant fibers, environmental industrial wastewater treatment, and pulp and paper production. PGLA-rep4 was previously generated as a modified alkaline pectin lyase with high specific activity at pH 11.0 and 70℃. However, the pre-constructed high-activity pectin lyase expression strains are still difficult to apply in industrial production due to their limited enzymatic activity. We hope to solve these problems by combining modern breeding techniques with high-throughput equipment to rapidly screen alkaline pectin lyase with higher enzymatic activity and lower cost. Methods: We fused the genes encoding PGLA-rep4 and fluorescent protein egfp using a flexible linker peptide and ligated them into a temperature-sensitive plasmid, pKD46. The constructed screening plasmid pKD46-PGLA-rep4-egfp was then transformed into an expression host and screened via flow-cytometric cell sorting coupled with UV mutagenesis. Results: Following mutagenesis, primary screening, and secondary screening, the high-expression strain, named Escherichia coli BL21/1G3, was obtained. The screening plasmid pKD46-PGLA-rep4-egfp was eliminated, and the original expression plasmid pET28a-PGLA-rep4 was then retransformed into the mutant strains. After induction and fermentation, pectin lyase activity in E. coli BL21/1G3 was significantly increased (1.37-fold relative to that in the parental E. coli BL21/PGLA-rep4 strain, p < 0.001), and the highest activity was 230,240 U/mL at 144 h. Genome sequencing revealed that genes encoding ribonuclease E (RNase E) and diadenosine tetraphosphatase (ApaH) of E. coli BL21/1G3 were mutated compared to the sequence in the original E. coli BL21 (DE3) strain, which could be associated with increased enzyme expression. Discussion: Our work provides an effective method for the construction of strains expressing pectin lyase at high levels.